Clinico-aetiological Analysis of Anaemia along with Haematological Parameters in Children and Adolescents: A Retrospective Study from a Tertiary Care Hospital, Chhattisgarh, India - Gyanesh Mishra; Rinu Dwivedi (Journal of Clinical and Diagnostic Research, 2022)
Introduction: Anaemia is defined as a decreased concentration of blood haemoglobin. World Health Organisation (WHO) estimates that 42% of children less than five years of age worldwide are anaemic and prevalence of anaemia in India in children 6-59 months for year 2019 was 53.4%. Childhood anaemia not only affects physical health but cognitive and social development as well. Aim: To determine various causes of anaemia in children in age groups 1-5 years, 6-12 years and 13 to 18 years and to determine clinical features and haematological investigations in moderate to severe anaemia. Materials and Methods: This retrospective, observational study was conducted in Department of Paediatrics, Shri Shankaracharya Institute of Medical Sciences, Bhilai, Charttisgarh, India, from September 2021 to December 2021. The data collection was done retrospectively over a period of two years, from September 2019 to September 2021 from patients case records which were available from Medical Record Department. A total of 300 patients from age one year to 18 years who were admitted in the paediatric ward with anaemia were included for study. Anaemia was defined and severity categorised based on WHO definition. The aetiology of anaemia was analysed based on Complete Blood Count (CBC) and investigations including serum ferritin, vitamin B12 level, bone marrow examination, High Performance Liquid Chromatography (HPLC) and other relevant investigations. Data was entered in a excel sheet and analysed using software Statistical Package for the Social Sciences (SPSS) version 21.0. Statistical test used was student’s t-test for paired and unpaired data for continuous variables. The p-value <0.05 was considered significant. Results: Out of total 300 patients, 148 (49.3%) were males and 152 (50.7%) were females. Most of the patients were in 1-5 years of age (45.6%), followed by 13-18 years age (29.4%) and 6-12 years (25%). Total 95 (31.6%) patients had mild, 112 (37.3%) had moderate and 93 (31%) had severe anaemia. The three most common causes of anaemia were iron deficiency in 77 patients (37.5%), haemolytic anaemia in 54 patients (26.3%) and vitamin B12 deficiency in 34 patients (16.5%). Mean Red Cell Distribution Width (RDW )(31.1±10.1%) values and mean of Mean Corpuscular Volume (MCV) (98.2±15.2 fL) were higher in vitamin B12 deficiency patients as compared to iron deficiency patients mean RDW (17.2±3.5%) and mean of MCV (58.14±7.3 fL), this difference was found to be significant with p-value <0.001. Conclusion: Most of the patients had moderate anaemia. Iron deficiency was most common cause of anaemia overall in children and especially below 13 years followed by haemolytic anaemia mainly sickle cell anaemia and Vitamin B12 deficiency anaemia. The MCV and RDW values from CBC can be used to identify two most common causes of nutritional anaemia.